Development of a core curriculum framework in cariology for U.S. dental schools (2016)
Maintenance of health and preservation of tooth structure through risk-based prevention and patient-centered, evidencebased disease management, reassessed at regular intervals over time, are the cornerstones of present-day caries management. Yet management of caries based on risk assessment that goes beyond restorative care has not had a strong place in curriculum development and competency assessment in U.S. dental schools. The aim of this study was to develop a competency-based core cariology curriculum framework for use in U.S. dental schools. The Section on Cariology of the American Dental Education Association (ADEA) organized a one-day consensus workshop, followed by a meeting program, to adapt the European Core Cariology Curriculum to the needs of U.S. dental education. Participants in the workshop were 73 faculty members from 35 U.S., three Canadian, and four international dental schools. Representatives from all 65 U.S. dental schools were then invited to review and provide feedback on a draft document. A recommended competency statement on caries management was also developed: "Upon graduation, a dentist must be competent in evidence-based detection, diagnosis, risk assessment, prevention, and nonsurgical and surgical management of dental caries, both at the individual and community levels, and be able to reassess the outcomes of interventions over time." This competency statement supports a curriculum framework built around five domains: 1) knowledge base; 2) risk assessment, diagnosis, and synthesis; 3) treatment decision making: preventive strategies and nonsurgical management; 4) treatment decision making: surgical therapy; and 5) evidence-based cariology in clinical and public health practice. Each domain includes objectives and learning outcomes.